NLRP3 inflammasome contributes to endotoxin-induced coagulation. Issue 214 (June 2022) - Shi, Jie; Tang, Yiting; Liang, Fang; Liu, Liping; Liang, Ni; Yang, Xinyu; Zhang, Ningjie; Yi, Zhonjie; Zhong, Yanjun; Wang, Wenhua; Zhao, Kai
Abstract: Introduction: Excessive activation of the coagulation cascades leads to life-threatening disseminated intravascular coagulation (DIC) in sepsis. Two recent studies by our group and others have both demonstrated the noncanonical inflammasome is pivotal for the endotoxin or gram-negative bacterial-induced coagulation. Based on this, we further evaluated the function of the NLRP3 inflammasome, the most studied inflammasome, in endotoxin-induced coagulation. Materials and methods: We established an endotoxin-induced coagulation model by intraperitoneal injection of sublethal doses of LPS in mice. Mice were sacrificed 8 h after injection and blood was collected for thrombin-antithrombin (TAT), plasminogen activator inhibitor-1 (PAI-1), prothrombin time (PT), D-dimer, IL-1β and tissue factor (TF) measurements by commercial ELISA. Lungs and livers were examined via HE staining images to determine injury scores and immunohistochemistry for TF expression and fibrin deposits. The role of NLRP3 activation was evaluated in wild-type (WT), Nlrp3 −/−, Asc −/− (apoptosis-associated speck-like protein containing a CARD), Caspase-11 −/− mice and 30 min after treatment with MCC950, a potent inhibitor of NLRP3. Western blotting and Q-PCR were performed to assess TF expression in the lungs and livers. To uncover the different effects of NLRP3 and Caspase-11, we also compared the time-dependent IL-1β release in LPS-treated Nlrp3 −/− and Caspase-11 −/− mice. Correlation analysis of TAT, PAI-1 were estimated the relationship of coagulation and release of IL-1β, as well as IL-1β and TF. Results: Inhibition of NLRP3 by MCC950 as well as NLRP3 or ASC deficiency decreased TAT, PAI-1, PT, D-dimer, and TF levels in blood and impaired the thrombus formation and fibrin deposition, as well as declined expression of TF in the liver and lung in endotoxin-induced coagulation but not caspase-11 deficiency. Impressively, IL-1β release is increased in LPS-treated Caspase-11 −/− mice, but not in Nlrp3 −/− mice. Moreover, the correlation analysis is indicated that downstream of the NLRP3 inflammasome, IL-1β expression, is positively correlated with TAT, PAI-1 and TF in blood circulation. Conclusions: The NLRP3 inflammasome contributes to endotoxin-induced coagulation by promoting TF expression at least in part through the induction of IL-1β release. These findings broadened our understanding of the mechanism of coagulation and implicated a possible therapeutic strategy for preventing coagulation in sepsis.